Pengaruh Pengembangan Karir Dan Budaya Organisasi Terhadap Kinerja Pegawai pada Dinas Sosial Kota Bima - Mulyani, Nana; Ikbal Irawan; Jaenab Jaenab (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of career development and organizational culture on employee performance at the Bima City Social Service. The research method used is quantitative with an associative approach. The sample in this study was 35 people who were civil servants. Data collection techniques were carried out using questionnaires, and data analysis included validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, and f-tests. The results of the study indicate that career development has a positive and significant effect on employee performance. Organizational culture also has a positive and significant effect on employee performance. Simultaneously, career development and organizational culture have a positive and significant effect on employee performance. These findings indicate the importance of training, fair career opportunities, and an open and collaborative work culture in improving employee performance. Therefore, the Bima City Social Service is advised to continue improving career development and strengthening an organizational culture that supports performance. In addition, this study also highlights the importance of management's role in creating an environment that supports career development and a positive organizational culture. Fair and transparent career development not only provides opportunities for employees to improve their skills and knowledge but also motivates them to contribute more to organizational goals. Likewise, an inclusive and collaborative organizational culture can increase mutual trust, effective communication, and cooperation among employees, thus creating a work environment conducive to improved performance. The research concludes that these two factors—career development and organizational culture—interact to optimize employee performance. Therefore, the Bima City Social Service needs to continue developing policies that support both aspects, such as regular training, fair promotion programs, and the development of a work culture that emphasizes collaboration and appreciation for employee performance.